To find the value of the expression, we need to subtract the second number from the first number.
First, let's convert both numbers to improper fractions:
-6 4/9 = -59/9
-1 1/3 = -4/3
Now, subtract the second number from the first number:
-59/9 - (-4/3) = -59/9 + 4/3
To add these fractions, we need a common denominator. The smallest number that both 9 and 3 divide into is 9, so we'll use that as the common denominator.
-59/9 + 4/3 = -59/9 + 4/3 * 3/3
= -59/9 + 12/9
= (-59 + 12)/9
= -47/9
Therefore, the value of the expression −6 4/9−1 1/3 is -47/9.
What is the value of the expression −6 4/9−1 1/3
1 answer